Development and fabrication of low-mass, low-power, internally-calibrated, MMIC-based millimeter-wave radiometers at 92 and 166 GHz - Lee, Alexander L., author; Reising, Steven C., advisor; Notaros, Branislav, committee member; Kummerow, Christian D., committee member; Kangaslahti, Pekka, committee member (Colorado State University. Libraries, 2012)
This thesis discusses the design, fabrication, and testing of two millimeter-wave internally calibrated MMIC based radiometers operating at 92 and 166 GHz. These laboratory prototype radiometers are intended to increase the technological maturity of the radiometer components and reduce the risk, development time and cost of deploying satellite based radiometers operating in the 90-170 GHz frequency range. Specifically, radiometers at similar frequencies are being considered on NASA's SWOT mission, planned for launch in 2020. The SWOT mission is an ocean altimetry mission intended to increase the Earth science community's knowledge of the kinetic energy in ocean circulation and mesoscale eddies as well as the vertical transport of heat and carbon in the ocean. These direct detection Dicke radiometers have two internal calibration sources integrated in the front end. These sources consist of a high excess noise ratio noise diode and a temperature controlled matched load. Internal calibration is a requirement on ocean altimetry missions to avoid the need for moving parts, which are necessary to accomplish external calibration. The index of refraction of the atmosphere depends on temperature and humidity. The variability of humidity in time and space is more difficult to measure and model than that of temperature. Changes in the index of refraction of the atmosphere add error to satellite based ocean altimetry measurements. Microwave radiometers have been used on altimetry missions to measure the amount of atmospheric water vapor, and this data is used to correct the altimetry measurements. Traditionally, microwave radiometers in the 18-37 GHz range have been used on these missions. However, due to the large instantaneous fields of view (IFOV) on the Earth's surface, land begins to encroach upon the radiometer's surface footprint at about 40 km from the coast. The emission from the land adds additional error to the radiometer measurements. The amount of error is unknown due to the highly variable emissivity of land. The addition of higher frequency millimeter-wave radiometers in the 90-170 GHz frequency range will reduce the IFOV on the Earth's surface and therefore enable atmospheric water vapor measurements closer to the coasts. The radiometers presented in this thesis are laboratory prototypes. They are intended to demonstrate new component technology and improve estimates of mass, volume, power consumption, and radiometric performance for future space-borne millimeter-wave radiometers.
Keywords: internal calibration; millimeter wave; MMIC; ocean altimetry; radiometer; wet path delay